DINAMIKA PEMANFAATAN TANAH ULAYAT DALAM PEMBANGUNAN PERUMAHAN: KASUS: DESA GERUNG SELATAN, LOMBOK BARAT - Perdana, Lalu Rizky Putra; Swasto, Deva Fosterharoldas (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
The construction of this housing is carried out as an effort to meet the demands of the needs of the community which is increasing and growing. All regencies/cities are quite intense giving permission to developers to build housing in their area. One of the most popular locations is the one located in the South Gerung area. In line with the development of regional development, it must be open to seeing the issue of existing progress, therefore as a superior area because of a district capital. The implication of the development of the region is the emergence of various problems including the conflict of spatial use that can threaten the continuity in the area. This makes a new conflict related to housing residents as a new citizen when the fellowship and so on, this will occur a problem or confusion related to its resolution. This study uses qualitative methods, the data obtained for this study are interviews and secondary data. The results of this study found a number of related conceptualizations of the first dynamics of factors, namely which discusses how the beginning of a conflict and what is behind this conflict occurs, the second dynamics of conflict is related to how the impact that occurs and is felt by the surrounding community in housing as a result of conflict And disputes occur so that they find the impact of periodic and temporary, the three dynamics of resolution related to conflict mediation and actors involved where in this section discusses how in the form of the Bale Mediation institution after previously mediating conflict in a personal way with the figures, and in this case involved There are also those from individuals and groups. Keywords: conflict and resolution, customary land, housing